Reducing Prejudice and Reinforcement of Religious Tolerance Across the Fictional World - Ita Rodiah; Nur Faiqoh (Vol. 1 No. 1 (2022): Proceeding of International Conference Cultures & Languages 2022, 2022)
In post-pandemic era, prejudice remains an important theme in public issues. Tensions between cultural, social, and even religious elements are still triggered by prejudice, especially religious prejudice. Even though conflicts occur due to a variety of factors, religion is frequently a significant factor. Religious issues frequently create religious intolerance. Religion is considered paradoxical (a paradox of faith) because it generates religious excitement (creating and even preventing prejudice formation) as well as moral and ethical decline. The imaginative world (literary works) is transformed into a communicative and contemplative medium, as well as a critical and reflective medium toward socio-cultural phenomena from/to the world of reality. Imaginary works become a medium of communication and peace-building for the development of religious tolerance through imaginary narratives that are able to present a diversity-oriented dialogue. This paper discusses on how Saddam Hussein’s novel ‘Ukhruj Minha Ya Mal’un’ reflects prejudice reduction. The texts shared a discourse on socio-cultural contact, inter-religious dialogue (inter-group friendship), inclusive theology, opposing prejudice, conflict resolution, individual personality, religious experience, and religious attitudes, which play important roles in the reinforcement of religious tolerance. Data on religious values (Islam) were collected from the novel’s text using the qualitative-interpretative method and Gordon Allport’s perspective on the nature of prejudice, and then explored using the technique of explication du texte. This paper argues that reinforcement of religious tolerance can be carried out continuously by discovering the fundamental values of religion and producing inclusive theological images so that they are more appreciative of diversity. The Implications of the findings of this study are expected to refute the assumption that religion is a final frontier (and/or has the potential prejudice) of personal prejudice, stereotype, and discrimination, with attitudes to faith driving negative perceptions more than ethnicity or nationality.